Analisa Kinerja Keuangan PT BTPN Tbk Periode 2015-2019 dengan POJK Nomor 4/POJK.03/2016 - Ega Virgiani; Dadang Hermawan; Rosma Pakpahan (Jurusan Akuntansi Politeknik Negeri Bandung, 2020)
In 2019, PT BTPN Tbk ranked seventh as the bank with the large asset. The purpose of ther esearch is to analyze financial performance at PT BTPN Tbk 2019 that determinate the health of the bank. This research used quantitative and secondary data from annual financial report during 2015-2019. Collecting data method is using literature study. This research using descriptive analysis with ratio: Liquidity Ratio (Quick Ratio, Loan to Fund Ratio (LFR) and Loan to Asset(LAR), Solvability Ratio (Return On Asset(ROA), ROE (Return On Equity), Net Interest Margin (NIM) and BOPO) and Rentability Ratio (Debt to Equity Ratio (DER) and Cash Adequacy Ratio (CAR)). The result of research show that financial performance of PT BTPN Tbk period 2015-2019 in good condition.